WORDWALL SEBAGAI MEDIA BELAJAR INTERAKTIF DARING DALAM MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MAHASISWA GEOGRAFI PADA MATA KULIAH GEOGRAFI DESA KOTA DI MASA PANDEMI - Windayani Ika Yunita Sari (LPPM Universitas Muhammadiyah Gorontalo, 2021)
This research was conducted with the aim of increasing student activities and learning outcomes in the implementation of online learning. The low activity and learning outcomes of students of the Geography Education study program at the State University of Gorontalo, in the Urban Village Geography course during the pandemic, became the basis of this research. This research is a classroom action research. The subjects of this study were students of the Class of 2019 totaling 65 people. Data collection techniques using observation and tests. Data analysis used quantitative and qualitative descriptive statistical analysis methods. From the results of observation data on student activities in the learning process, it shows an increase from cycle I to cycle II. with the test results at the end of the first cycle that the percentage of completeness was 45% and there was an increase in the percentage at the end of the second cycle (97%). This shows that the target percentage of students' completeness has exceeded the learning achievement limit for Graduates. The use of website-based Wordwall application media can increase the activities and learning outcomes of students of the Geography Education study program at the State University of GorontaloPenelitian ini dilakukan dengan tujuan untuk meningkatkan aktifitas dan hasil belajar mahasiswa dalam pelaksanan pembeljaran daring. Rendahnya aktifitas dan hasil belajar mahasiswa program studi Pendidikan geografi Universitas Negeri Gorontalo, pada mata kuliah Geografi Desa Kota pada masa pandemi menjadi dasar penelitian ini. Penelitian ini merupakan suatu penelitian tindakan kelas. Subjek dari penelitian ini adalah mahasiswa Angkatan 2019 yang berjumlah 65 orang. Penelitian ini di laksanakan pada kuliah daring di Universitas negeri Gorontalo. Teknik pengumpulan data menggunakan observasi dan tes. Analisis data menggunakan metode analisis statistika deskripstif kuantitatif dan kualitatif. Dari hasil data observasi aktiftas mahasiswa dalam proses pembeljaran menunjukan adanya peningkatan dari siklus I ke siklus II. dengan hasil tes pada akhir siklus I bahwa persentase ketuntasan sebsar 45% dan mengalami peningkatan persentase pada akhir siklus II sebsar (97%) . hal ini menunjukan target persentase ketuntasan mahasiswa sudah melebihi batas Capaian pembelajaran Lulusan. Penggunaan media belajar aplikasi Wordwall berbasis website dapat meningkatkan aktifitas dan hasil belajar mahasiswa program studi Pendidikan geografi Universitas Negeri Gorontalo